Educational Marginalization in Northern Kenya - Hussein, Adan Maalim (Journal of Education and Practice, 2025)
Purpose: This study examined the persistent educational marginalization of youth in Northeastern Kenya, a region historically overlooked since the colonial era. The study also looks at the government's and non-governmental organizations' attempts and opportunities to enhance the education sector using the devolution structure included in Kenya's new constitution. Methodology: A mixed-methods research design was proposed to investigate these issues comprehensively. Quantitative data, analyzed through descriptive statistics, explored enrollment patterns, dropout rates, and resource distribution, while qualitative thematic analysis captured the lived experiences of affected communities, cultural attitudes towards education, and the effectiveness of government policies. Findings: Findings indicated that insecurity, forced migration, and a lack of culturally sensitive policies perpetuate educational inequality in Northeastern Kenya. Limited awareness of the region’s unique needs further hampers development efforts. Unique Contribution to Theory, Practice and Policy: The study recommends leveraging Kenya’s devolved governance structure to direct targeted resources, retain teachers, and foster community engagement. Addressing security concerns and integrating cultural practices into education policy are vital for improving educational outcomes in this marginalized region.